Research on Online Hate Speech Detection from Popper and Kuhn's Philosophical Perspective - Cahyana, Rinda; Fitriani, Leni; Setiawan, Yudi; Mahayana, Dimitri (Puslitbang Akademi Relawan TIK Indonesia, 2024)
The negative impact of spreading hate speech on social media has prompted various parties to intervene. Computer science researchers have conducted experiments to find solutions for automated intervention by applying artificial intelligence, such as machine learning and deep learning. The fulfillment of the theory of truth makes the machine learning paradigm considered by scientists to solve problems. However, the increasing size of social media data has shifted its paradigm to deep learning. Deep learning becomes a new normal science after completing the task of classifying hate speech well on a large amount of data. However, any approach will be an anomaly when it cannot complete the task. The accessibility of research resources makes it easier for researchers to determine the nature of their experiments, whether scientific or pseudo-science.